Energy savings approaches for high-tech manufacturing factories. (February 2020) - Hu, Shih-Cheng; Lin, Tee; Huang, Shao-Huan; Fu, Ben-Ran; Hu, Ming-Hsuan
Abstract: This study integrates a fab energy simulation (FES) tool and energy conversion factors to analyze energy consumption and identify energy savings opportunities of high-tech manufacturing factories. The data used is the 169, 124 MW h annual energy consumption of a Taiwanese semiconductor manufacturing fab. We proposed a compressed/clean dry air (CDA) system as a two-pressure system using a heated-type dryer. The proposed method achieved 3050 MW h as the highest energy savings in the CDA system compared to the original fab data. The results also indicate that lowering the make-up air unit (MAU) operating temperature caused significant energy savings for the high-temperature water chiller system. When the outlet air temperature of the MAU system was 14 °C, the maximum energy savings were 3532 MW h. In addition, the process cooling water (PCW) system could potentially save energy by reducing the pumping head of water in its open system. Therefore, we suggested a closed PCW system that reached a maximum energy saving of 1541 MW h.